Conversion efficiency of fir roundwood into sawlogs - Brandstetter, M., Zeleniuc, O., Pei, G., and Campean, M. (My University, 2020)
The objective of this research was to quantitate the amount of wood loss that occurs during the processing of freshly harvested fir roundwood into sawlogs. The influence of the felling damages and various growth defects, e.g., curvature, taper, and forked growth, were taken into consideration. The causes of wood loss and wood volume reduction during the three primary operations of this processing chain, under the considered limited conditions, were established. The greatest wood volume reduction recorded was an 11% decrease, which was caused by the crosscutting of the stems into shorter logs. Additional wood volume reductions were due to the selection (grading) of the sawable logs and to debarking (7% and 6%, respectively). Some recommendations, in terms of industrial applicability, i.e., methods to reduce the amount of wood loss, were also formulated.